2019
DOI: 10.1130/ges02013.1
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns of erosion and landscape evolution in a bivergent metamorphic core complex revealed by cosmogenic 10Be: The central Menderes Massif (western Turkey)

Abstract: In extensional provinces with low-angle normal faulting (such as the Aegean region), both tectonic processes and erosion induce landscape change, but their interaction during the evolution of topography and relief accompanying continental extension has rarely been addressed. Here we present local and catchment-wide 10Be erosion rates that document the spatial pattern of erosion in the central Menderes Massif, a metamorphic core complex consisting of two asymmetric mountain ranges (Bozdağ and Aydın) bound by de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 112 publications
2
22
0
Order By: Relevance
“…The relatively higher pattern of catchment-wide erosion rates in S3 and S5 likely confirms this view. The reason why previous 24 , 28 studies did not find any relationship between tectonics and catchment-wide erosion is probably that these earlier studies focused mostly on the western part of the range. Our new catchment-wide erosion data from the missing parts of the range have indicated that catchment-wide erosion mostly shows a pattern compatible with tectonic uplift across the range.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…The relatively higher pattern of catchment-wide erosion rates in S3 and S5 likely confirms this view. The reason why previous 24 , 28 studies did not find any relationship between tectonics and catchment-wide erosion is probably that these earlier studies focused mostly on the western part of the range. Our new catchment-wide erosion data from the missing parts of the range have indicated that catchment-wide erosion mostly shows a pattern compatible with tectonic uplift across the range.…”
Section: Discussionmentioning
confidence: 91%
“…The alluvial fans are aligned along a segmented normal fault 23 , the catchments have not been glaciated over the duration of alluvial fan deposition 24 , the climate, and vegetation, within each catchment-alluvial fan system are very similar, and there is a mixture of mostly metamorphic and plutonic lithologies with some sedimentary rocks that are mapped 25 – 27 . Furthermore, the area offers a wide range of river incision and catchment-wide erosion rates 24 , 28 , as shown here. We interpret these as a function of differential rock uplift between the footwall catchments and hanging wall alluvial fan systems.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Geological units are simplified from Kent et al (2021) with additional mapping of Holocene lake deposits from Süzen, Toprak and Rojay (2006). Numbers in bold indicate rivers sampled for cosmogenic radionuclides (CRN) either in this study (Table 1) or by Heineke et al (2019) or Buscher et al (2013) (Table 3) topographic graben (Çiftçi & Bozkurt, 2009). In the uplifted footwall of the active fault are friable sedimentary rocks deposited originally on the hanging wall of the Gediz detachment.…”
Section: Study Areamentioning
confidence: 99%